2011
DOI: 10.1016/j.archger.2009.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Body position and cardio-respiratory variables in older people

Abstract: Background: Older people are placed in different body positions for medical, nursing and physiotherapy intervention.Objective: To investigate the effect of body position on cardio-respiratory variables in active older people.Design: Experimental laboratory study.Setting: Research was undertaken at the James Cook University, Physiotherapy Clinic.Subjects: Twenty-six active people aged 60 years and over.Methods: Heart rate, systolic and diastolic blood pressure and oxygen saturation were measured every two minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…13,14,16,19 Yet, three other randomized studies found nonsignificant differences in SBP between body positions. 15,17,18 Similarly, in line with the present findings, DBP is more likely to be lower in the supine position (five out of seven randomized studies [13][14][15][16][17][18][19] ), a finding that is also consistent in most of the non-randomized studies. 20,21,24,25,29,30 Regarding MBP, one randomized 18 and two non-randomized studies 25,29 suggest that it is higher in the sitting position whereas another non-randomized study reported higher MBP in the supine position; 22 the rest of the studies do not provide data for MBP.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…13,14,16,19 Yet, three other randomized studies found nonsignificant differences in SBP between body positions. 15,17,18 Similarly, in line with the present findings, DBP is more likely to be lower in the supine position (five out of seven randomized studies [13][14][15][16][17][18][19] ), a finding that is also consistent in most of the non-randomized studies. 20,21,24,25,29,30 Regarding MBP, one randomized 18 and two non-randomized studies 25,29 suggest that it is higher in the sitting position whereas another non-randomized study reported higher MBP in the supine position; 22 the rest of the studies do not provide data for MBP.…”
Section: Discussionsupporting
confidence: 91%
“…A series of studies [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] have shown that body posture affects bBP values. In most recommendations [31][32][33][34] as well as in most clinical trials and daily clinical practice, the sitting position for bBP measurement is most commonly applied.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the intergroup analysis has shown that there were significant differences in PEF between before and after the exercise. Changes in posture may affect cardiovascular, digestive, respiratory, and musculoskeletal systems and should therefore be considered as important in medical management and physical therapy [14]. Correction and respiratory therapy should be performed because scoliosis patients have weakened respiratory muscles due to curvature of the thoracic spine, which reduces cardiopulmonary function [15].…”
Section: Discussionmentioning
confidence: 99%
“…For this topic, Gordon et al (2011) reported that lateral positions produce significantly lower diastolic, systolic, and mean arterial blood pressure than does the supine position. Furthermore, Leung et al (2003) pointed out that patients with congestive heart failure avoid the left lateral position during sleep to prevent discomfort from an enlarged apical heart.…”
Section: Introductionmentioning
confidence: 98%
“…Many methods have been used to improve sleep quality including sleep hygiene education and behavioral therapy Kaku et al, 2012), doing a short afternoon nap (Kaida et al, 2012), using a suitable pillow with appropriate support to reduce neck and shoulder pain (Lavin et al, 1997), and keep in a certain sleep positions (Gordon et al, 2011;Leung et al, 2003). For this topic, Gordon et al (2011) reported that lateral positions produce significantly lower diastolic, systolic, and mean arterial blood pressure than does the supine position.…”
Section: Introductionmentioning
confidence: 98%